Effect of Annealing Temperature on the Film CIGS Solar College and the Preparation by Evaporation Precipitation Method Thermal - Yassin, Ali Lafta Khalaf; Jweid, Ali Hashim Hadi; Kahdam, Aseel Haitham; Kareem, Noor Hadi; Abdullah, Ali Khaled (American Journal of Botany and Bioengineering, 2024)
This work aims to use renewable energy as clean energy and environmental health and to stay away from pollutants. Recently, and since the industrial revolution, the climate has been increasingly affected by human activities. Fossil fuels are one of the reasons that lead to global warming. The need to search for alternative sources of energy has emerged. Solar energy is one of the alternatives to obtain clean energy. When photovoltaic panels are installed at a specific tilt angle so that they are exposed to the greatest possible amount of solar radiation throughout their operating period. Scientists have found that the productivity of photovoltaic panels can be increased by making them maintain a vertical angle with the radiation falling on them to a greater extent, and this is achieved through the solar tracker (solar tracking devices) where a smart system was created to track solar radiation that works with two axes, one in the vertical direction and the other in the horizontal direction, and it was compared to a fixed system and in different conditions and we obtained the best results with tracking where the use of the solar tracker can lead to an increase in energy production from the solar cell panel by about 30% to 60% compared to the fixed solar panel system and because the climate of Iraq is sunny most days of the year, especially in the summer, where the conditions are suitable for building solar energy systems and relying on them to meet its energy needs.